The Influence Of Communication And Training On The Peformance Of Employees In The Assembling And Sewing Section At PT.Adis Dimension Footwear Regency - Dian, Dian; Purwanto, Agus; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the extent of the influence of simultaneous communication and training on the performance of employees in the Assembling and Sewing departments at PT. Adis Dimension Footwear Balaraja-Tangerang.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Assembling and Sewing departments at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 100 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population of 100 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, communication significantly influences the performance of employees in the Assembling and Sewing departments at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (8.916>1.985) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, training significantly influences the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (3.513>1.985) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected.(3) Simultaneously, communication and training significantly influence the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (43.213>3.09) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that communication and training variables, both partially and simultaneously, have a significant influence on the performance of employees in the Assembling and Sewing divisions at PT. Adis Dimension Footwear Balaraja-Tangerang.